2019
DOI: 10.1039/c9nr01192g
|View full text |Cite
|
Sign up to set email alerts
|

Water-resistant AgBiS2 colloidal nanocrystal solids for eco-friendly thin film photovoltaics

Abstract: The AgBiS2 nanocrystal solar cells exhibit no drop in their device performance before and after the water treatment, suggesting that AgBiS2 nanocrystal solids are highly water-resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“… 34 Elemental compositions were also confirmed by XPS that Modified method provides the resultant AgBiS 2 NCs with the higher amount of Ag element, indicating the average size reduction, better stoichiometry and energetically more stable surface termination, compared to those in Control method (Figure S5 and Table S1). 28,30,34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 34 Elemental compositions were also confirmed by XPS that Modified method provides the resultant AgBiS 2 NCs with the higher amount of Ag element, indicating the average size reduction, better stoichiometry and energetically more stable surface termination, compared to those in Control method (Figure S5 and Table S1). 28,30,34 …”
Section: Resultsmentioning
confidence: 99%
“…34 Elemental compositions were also confirmed by XPS that Modified method provides the resultant AgBiS 2 NCs with the higher amount of Ag element, indicating the average size reduction, better stoichiometry and energetically more stable surface termination, compared to those in Control method ( Figure S5 and Table S1). 28,30,34 In addition, we increased the injection temperature of the sulfur precursor solution up to 130 C to identify the effect on the size-distribution of the AgBiS 2 NCs. HR-TEM images and size-distribution histograms showed that the overall size-distribution of AgBiS 2 NCs was improved with the Modified method because of the reduced variation in the concentration of oleic acid (see Figure S6).…”
Section: F I G U R E 1 Hr-tem Images Of Agbis 2 Ncs Prepared By Variomentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, a number of Ag-Bi-S QDSCs emerge. [145][146][147] [41] Copyright 2016, Macmillan Publishers Ltd.…”
Section: Ternary Ag-bi Chalcogenidesmentioning
confidence: 99%